2009
DOI: 10.17221/19/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and endocrine characteristics of pregnancy toxemia in the ferret

Abstract: Metabolic and endocrine characteristics of pregnancy toxemia are well documented in small ruminants, but less known in other species. The objective of this study was to measure plasma levels of certain metabolites and metabolic hormones related to the energetic status in blood from sick and healthy, non-pregnant (control) ferrets. Blood was collected from moribund, hypothermic, late pregnant females suffering from pregnancy toxemia (n = 4) and from healthy female ferrets (n = 14) to measure glucose, ketone (βO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Insulin, T 4 , and T 3 are important hormones in the regulation of energy homeostasis. The decreases in T 4 in experimental pregnancy toxemic goats in the present study were similar to that recorded in ewes [ 5 ] and ferret [ 31 ] with pregnancy toxemia.…”
Section: Discussionsupporting
confidence: 90%
“…Insulin, T 4 , and T 3 are important hormones in the regulation of energy homeostasis. The decreases in T 4 in experimental pregnancy toxemic goats in the present study were similar to that recorded in ewes [ 5 ] and ferret [ 31 ] with pregnancy toxemia.…”
Section: Discussionsupporting
confidence: 90%
“…Insulin, T4, and T3 are important hormones in the regulation of energy homeostasis. The decreases in T4 in pregnancy toxemic ewes in the present study were similar to that noticed in ewes (Kulcs´ar et al, 2006) Goats (Hefnawy et al, 2011) and ferret (Prohaczik et al, 2009) with pregnancy toxemia. And the significance decreases in T3 is disagreed with (Hefnawy et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the serum urea and creatinine levels showed significant increase in pregnancy toxemic goats, which might be attributed due to involvement of the kidney in the pathogenesis of caprine pregnancy toxemia (El-Sebaie, 1995, Hefnawy et al, 2011Marteniuk and Herdt, 1998;Nagamani et al, 1996;Ramin et al, 2005). The significant decrease in the serum levels of sodium, Akraiem et al 163 potassium and calcium as well as significant increase in the packed cell volume (PCV) in the pregnancy toxemic goats indicated that there were disturbances in the electrolytes and some minerals which may be attributed to stress of starvation, dehydration and involvement of the kidney in the pathogenesis of caprine pregnancy toxemia (Marteniuk and Herdt, 1988;Hefnawy et al, 2011;Prohaczik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%